Making Political Tourism As an Alternative Model for Hawaii Indigenous Development - Wilmar Salim (Centre For Tourism Planning and Development, 2012)
The current tourism business model, which is visitor-centered, shows how tourism has strong negative impacts to the host and the place. It happens in many places in the world where tourism business is run by outsiders or with outside capital, and creating conflict with local population. Political tourism is an alternative to the current business model because it looks at the business from the other side: the host-place-centered. Political tourism can be seen as the first step in